Situated Learning: Optimizing Experiential Learning through God-given Learning Community - Kemp, Stephen (Christian education journal, 2010)
This article explores the educational concept of experiential learning, particularly in terms of service learning and situated learning. It proposes an alternative definition of an academic learning community, namely the role of primary social relationships as God-given contexts for learning It concludes with practical application of the enormous potential for accomplishment of educational objectives through situated learning.